Pengaruh Faktor Risiko terhadap Efek Samping Hipotensi Ortostatik pada Pasien Hipertensi dengan Komorbid Diabetes Mellitus - Utami, Primanitha Ria; Pratiwi, Elasari Dwi; Ayuning Tiyas, Danur Sukma (Universitas Hamzanwadi, 2026)
Orthostatic hypotension is a common side effect of antihypertensive therapy that can lead to serious outcomes such as falls, injuries, and death. The risk increases in patients with comorbidities like diabetes mellitus, which affect autonomic regulation and often require multiple medications (polypharmacy). This study aimed to assess the influence of risk factors gender, age, duration of use, body mass index, and polypharmacy on the incidence of orthostatic hypotension in hypertensive patients with comorbidities at the Lamongan District Health Center. Using a cross-sectional design, 78 Prolanis program participants were observed from January to March 2025. Data were collected through direct observation, medical records, and the Naranjo algorithm questionnaire, then analyzed with Spearman Rank correlation. Results showed that most respondents experienced possible (41.03%) to very certain (39.74%) side effects of orthostatic hypotension linked to antihypertensive use. Age (ρ=0.698; p=0.000), gender (ρ=0.308; p=0.006), and polypharmacy (ρ=0.277; p=0.014) were significantly associated with orthostatic hypotension, with age as the strongest factor. Duration of use (ρ=0.122; p=0.287) and body mass index (ρ=−0.006; p=0.961) showed no significant correlation. These findings highlight the need for heightened vigilance in elderly patients and those on multiple medications to prevent orthostatic hypotension. Further studies with larger samples and longer follow-up are recommended. Educating patients on proper medication use is crucial to reduce adverse effects.